VENTURE INNOVATIVE COMPANY DEVELOPMENT STRATEGY - A. V. Apollonov (Модернизация, инновация, развитие, 2016)
Innovative companies, venture companies included, serve as locomotives of the growth of national economics. However, they are formed and operate under conditions of uncertain external and internal environment; therefore, certain strategic issues of their development can not beaddressed proceeding from traditional methods based on cash-flow discounting models. Best venture innovative company development strategy may be worked on the basis of the strategic capabilities method in conjunction with the theory of games and the real options approach. This is an incessant innovation method that unites approaches based on external and internal environment factors.